Treatment Outcome in Bilateral Cleft lip and Palate Patients Evaluated With the Huddart-Bodenham Scoring System and the Bilateral Cleft lip and Palate Yardstick: A Systematic Review. (November 2022) - Kuang, Wenying; Aarts, Miranda; Kuijpers-Jagtman, Anne Marie; He, Hong; Ongkosuwito, Edwin M.
Objectives: To assess treatment outcome (transversal and sagittal dental arch relationships) and its determinants in complete bilateral cleft lip and palate (BCLP) evaluated with the modified Huddart-Bodenham scoring system and the BCLP Yardstick. Materials and methods: Multiple electronic databases were searched without time limitation. Randomized clinical trials, cohort and case control studies using BCLP Yardstick and/or modified Huddart-Bodenham system to judge treatment outcome of patients with BCLP were included. The Risk of Bias in Nonrandomized Studies of Interventions tool and Grading of Recommendations, Assessment, Development, and Evaluation was used. Results: Of the 528 studies identified by the electronic search, only eight retrospective studies met the inclusion criteria and were included. A total of 12 cleft centers were represented. All treatment protocols differed and background information was underreported. The results for the BCLP yardstick showed that all except the centers in New Zealand had a mean score lower than 3, indicating good treatment results. However, these studies had a moderate to high risk of bias. The modified Huddart-Bodenham scores were negative in all studies. No further meta-analysis was done due to heterogeneity and high risk of bias. The quality of evidence was graded as very low. Conclusion: Results for the dental arch relationship of studies in complete BCLP and possible determinants were not synthesized due to very low quality of evidence. Clinical research for patients with BCLP should focus on sound methodological designs to enable evidence-based decision making to improve treatment for patients with BCLP and thereby hopefully their quality of life.